The Impact of the COVID-19 Pandemic on Banking Liquidity: A Case Study of Various Bank Types in Indonesia - Riza, Mukaffi; Mawardi, Wisnu (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
This study aims to examine the condition of banking liquidity in Indonesia during the COVID-19 pandemic, utilizing linear regression to analyze factors influencing the liquidity of commercial banks in Indonesia from March 2020 to June 2023. The dependent variable used is the Loan Deposit Ratio (LDR), while the independent variables include Capital Adequacy Ratio (CAR), Return on Assets (ROA), Non-Performing Loans (NPL-gross), and Credit Restructuring Ratio to total Credit. The results reveal that CAR has a significant negative effect on the liquidity of Regional Development Banks (BPD), State-Owned Enterprises (BUMN), Private Banks, and Overseas Bank Branch Offices (KCBLN). Conversely, ROA has a positive and significant impact on state-owned banks but is not significant for BPD, private, and KCBLN banks. The NPL ratio does not significantly influence liquidity across all types of banks. Credit Restructuring Ratio negatively affects BPD and positively affects KCBLN, but it does not have a statistically significant effect on State-Owned and Private Banks. This research is unique as it is the first to examine commercial banks in Indonesia during the pandemic, providing valuable insights into the factors affecting bank liquidity during this period. The findings highlight the importance of maintaining adequate capital and profitability to support bank liquidity, especially during economic crises.